APOBEC3B gene overexpression in non-small-cell lung cancer - SASAKI, HIDEFUMI (D.A. Spandidos, 2014)
Recent study results have demonstrated that a subclass of apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like (APOBEC) cytidine deaminase may induce mutation clusters in various types of cancer. From the Cancer Genome Altas, an APOBEC mutation pattern was identified in bladder, cervical, breast, head and neck and lung cancers. In the present study, APOBEC3B mRNA expression was investigated using quantitative reverse transcription-polymerase chain reaction (RT-qPCR) assay using LightCycler in surgically treated non-small-cell lung cancer (NSCLC) cases. Additionally, 88 surgically removed Japanese NSCLC cases were analyzed for mRNA level. The results showed that APOBEC3B/β-actin mRNA levels were significantly higher in lung cancer (1,598.481±6,465.781) when compared to adjacent normal lung tissues (2,116.639±8,337.331, P=0.5453). The tumor/normal (T/N) ratio of APOBEC3B/β-actin mRNA levels was not different within the gender, age, smoking status and pathological stages. The T/N ratio of APOBEC3B/β-actin mRNA levels was not significantly different in epidermal growth factor receptor (EGFR) or Kras mutation-positive cases as compared to the wild-type cases.